FDE index for goodness-of-fit between measured and calculated response signals. - Dragovich, Jeff J. (Earthquake engineering & structural dynamics.)
A method is presented for determining the goodness-of-fit between measured and calculated structural response signals. The method is termed as the frequency domain error (FDE) index, which is a value between 0 and 1 where zero indicates a perfect correlation. The FDE is calculated from the Fourier spectra of the measured and calculated waveforms, using a relatively simple calculation procedure, readily implemented using standard fast Fourier transform (FFT) libraries. The FDE is demonstrated herein using three different types of problems: simple harmonic waves, a large number of earthquake response simulations, and a set of limited simulations. Along with the FDE concept, effective methods for displaying the results are presented.